Evaluasi Kinerja Badan Pengelola Keuangan dan Aset Daerah Kota Padang Menurut Perspektif Balanced Scorecard - Diga Putri Oktaviane (Faculty of Social Science, Universitas Negeri Padang, 2021)
Each public sector organization was given an annual budget by the government which was used based on the programs launched, so that the vision and mission of the organization could be achieved properly. So far, the evaluation of organizational performance was assessed only on the basis of financial aspects, through financial reports that were provided annually by related agencies or agencies to the Padang City government and similar things were also carried out by the Regional Financial and Asset Management Agency of Padang City. Meanwhile, to assess whether a performance was good or not, it must also be measured based on other criteria, such as performance evaluation using the balanced scorecard method. This research was conducted through a descriptive study with a qualitative approach. Data collection techniques used in this study were interviews and documentation studies. The technique used to measure employee performance was balance scorecard method. Then the data were analysed through manual data analysis procedure. The results showed that in terms of budget management, the Padang City Financial and Asset Management Agency has not fully implemented the balance scorecard method in its performance.